Analysis of Service Quality Using Service Quality and IPA Methods at XYZ Cafes - Setyo, Faris Aulia Dwi; Andesta, Deny (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
XYZ Cafe is an MSME business in Gresik Regency with a target market of teenagers and surrounding office employees. Cafe management evaluates cafe services for consumer complaints, which decreases the number of cafe visitors. Service quality is essential in marketing current products so that products can be well received in the market. The method used to determine the quality of service is service quality while determining the service attributes that need to be improved using the importance-performance analysis method. The quality of service provided by the XYZ Gresik cafe is based on service quality. From the results of the IPA analysis, the results of quadrants I, II, have relatively high demand, and quadrants III, IV, have relatively low demand with a relatively high level of satisfaction, so it is considered excessive. And from the GAP calculation results using the service quality method has a negative value.